2013
DOI: 10.1007/s00167-013-2779-2
|View full text |Cite
|
Sign up to set email alerts
|

T2 values of articular cartilage in clinically relevant subregions of the asymptomatic knee

Abstract: Significant differences in mean T2 values and texture parameters were found between subregions in this carefully selected asymptomatic population, which suggest that there is normal variation of T2 values within the knee joint. The clinically relevant subregions were found to be robust as demonstrated by the overall high repeatability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 39 publications
1
32
1
Order By: Relevance
“…On the other hand, the lateral condyle has an oval or box‐like shape, and showed a sharp and narrow peak at +54° in the deep layer in our image‐processing manner using circle‐fitting algorithm. T 2 values at the trochlea were higher than those of the medial and lateral condyle, as previously reported . The higher T 2 value at the lateral condyle than the medial condyle in the superficial layer may be explained by the basis that the medial condyle has a wider weight‐bearing area than the lateral condyle, and that weight‐bearing areas have lower T 2 values than nonweight bearing areas .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…On the other hand, the lateral condyle has an oval or box‐like shape, and showed a sharp and narrow peak at +54° in the deep layer in our image‐processing manner using circle‐fitting algorithm. T 2 values at the trochlea were higher than those of the medial and lateral condyle, as previously reported . The higher T 2 value at the lateral condyle than the medial condyle in the superficial layer may be explained by the basis that the medial condyle has a wider weight‐bearing area than the lateral condyle, and that weight‐bearing areas have lower T 2 values than nonweight bearing areas .…”
Section: Discussionsupporting
confidence: 78%
“…Surowiec et al reported significant differences in mean T 2 values between 21 subregions in healthy volunteers (range: 41.7–54.2 msec), suggesting that there is a normal variation of T 2 values within the knee. T 2 values of the three anatomical landmarks in our study were similar to those of previous studies (range: 44.3–52.3 msec) . Shiomi et al reported the 3D distribution of T 2 values of the entire femoral cartilage in healthy volunteer knees, in which cartilage T 2 values for the internal half of the weight‐bearing zone covered by meniscus were significantly higher than those in all other zones within both the medial and lateral condyles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, focusing only on weight‐bearing medial and lateral regions limits the generalizability of our results. As Surowiec et al have demonstrated, T 2 values and texture features vary naturally between the different anatomical regions within the knee joint . To acquire comprehensive understanding over the whole knee cartilage, all regions should be studied.…”
Section: Discussionmentioning
confidence: 99%
“…While different options exist for the treatment of OA, the efficiency and the implementation of treatment strategies to slow or to stop progression of the disease depend on early and accurate detection of the stage of OA [5].…”
Section: Introductionmentioning
confidence: 99%